Manitoba Public Libraries Response to the Early Stages of COVID-19 - Macdonald, Kerry; Robert, Andrew; Bannerman-Gobeil, Breanne; Bee, Richard; Chorney, Alan; Heinrichs, Caralie; Lee, Stacey; Murray, Kelly; Sucha, Melanie (Partnership, 2021)
Like many libraries across Canada, Manitoba public libraries have grappled with the challenges that COVID-19 has presented. Libraries have struggled to remain operational and offer a high level of service to patrons within the constraint of public health orders, all the while ensuring the safety and employment of their staff. Within the ever-changing environment of COVID-19, the Manitoba Library Association recognized the need to gather information from the library community in order to better position themselves to lend support and in an attempt to bridge information gaps. This article describes a study conducted by the Manitoba Library Association whereby fifty-five Manitoba public libraries were surveyed to identify how they were responding to COVID-19 and what their needs might be. The survey questions were divided into 6 sections (facilities, services, communications, staffing, connecting, wrap-up) and the results provide information and insight into how the Manitoba library community has dealt with the pandemic. More importantly, the results can serve to guide other libraries in decision-making and preparation for a pandemic.